Upaya UPAYA MENINGKATKAN TEKNIK PASSING ATAS BOLA VOLI PADA SISWA KELAS XI DI SMA NEGERI 9 SEMARANG MELALUI PERMAINAN BOLA BERACUN DALAM PEMBELAJARAN PJOK - Dika Pradana, Aditya; Wiyanto, Agus; Ibnu Fatkhu Royana (Prosiding Seminar Nasional Pendidikan Profesi Guru, 2025)
This study aims to improve the overhead passing technique in volleyball among eleventh-grade students at a public senior high school in Semarang through the application of a modified poison ball game. The main problem addressed in this research is the low level of students' basic passing skills, indicated by their low average scores and achievement rates. The study was conducted through two cycles of classroom action research, consisting of planning, implementation, observation, and reflection stages. Data were collected using observation and practical performance tests. The results showed an improvement in the average score from 58.06 in the initial stage to 70.08 in the first cycle, and further to 78.19 in the second cycle. The percentage of mastery learning also increased from 27.78% in the pre-cycle to 38.89% in the first cycle, and reached 83.33% in the second cycle. It is concluded that learning through the poison ball game creates a more active and enjoyable environment and effectively enhances students’ basic overhead passing skills in physical education learning.